Economic burden of diabetic care in government health facilities in Selangor - Sharifa Ezat WP,; Azimatun NA,; Amrizal MN,; Rohaizan J,; Saperi BS, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Background : The worldwide prevalence of diabetes is increasing, as is the demand for and cost of medical care. Diabetic Mellitus (DM) prevalence in Malaysia rose from 6.3% of the population in 1986 to 8.3% in 1996 and costs need to be managed more effectively. Objective : To estimate the financial burden of diabetic care, including providers’ and patients’ costs in government facilities in Selangor and to determine factors influencing cost of diabetic care. Methodology : A cross-sectional study was conducted from September to November 2005 among Hospitals with and without Specialist and Health Clinics. Total sample of 361 subjects with type 2 diabetes representing both inpatient and outpatient were chosen randomly. Results were analyzed using SPSS version 13.0. Results : The average cost for a diabetic patients’ admission in a Hospital with Specialist was RM1951 and RM1974 for patient admitted in a Hospital without Specialist and these cost difference was not statistically significant (p>0.05). Providers’ mean cost for outpatient care was RM772.69 and RM761.07 respectively for Hospital with Specialist and Hospital without Specialist per year. As for the health clinics the average providers’ cost for a patient was RM385.92 per year. The cost difference was statistically significant (p<0.05). Patient’s mean cost was RM68.77 in Hospital with Specialist, RM71.73 in Hospital without Specialist and RM72.11 in Health Clinics and the cost difference from the patient’s perspective was statistically not significant (p>0.05). The mean total costs of outpatient care were RM841.46, RM832.80 and RM458.01 per year for Hospital with Specialist, Hospital without Specialist and Health Clinics respectively. Level of care and length of stay were the influencing factors for inpatient provider’s cost. The overall provider’s cost for outpatient diabetic care was influenced by level of care, number of visits and complications. Cost of treating diabetes mellitus year 2004, was estimated at RM18,956,021.51 which was equivalent to 3.3% of total state health expenditure. Conclusion : As much as 60.2 % was spent on management of outpatient diabetic care and 39.8% for management of inpatient diabetic care. Financial burden of diabetic care is predominantly for outpatient care. Therefore, effective and efficient management of outpatient care is needed to improve allocate efficiency, equity, accessibility and appropriateness of the health care system so that the health care services delivered to the nation are of good quality.